Ejidos e comunidades agrárias em Oaxaca, México: um estudo histórico, legal e da realidade atual - Cruz, Alida Corey Arango (2016)
Mexico has three types of land ownership or land tenure regarding rural land; private, state, and what is called as social property. This paper studies the social property in Mexico, which consists of two types, the ejido and agrarian community; It is about a historical literature study as to the notions of ejido and community, and the formation of legal regulatory framework to the present; it analyzes how the ejidos and communities are distributed in Mexico, first comparing quantitatively the dynamics of these with the provisions of the law and, later, through a multiple-case study to contrast the agrarianl framework with reality in the ejidos and communities. The field study was conducted in the town of Tlacolula de Matamoros, Oaxaca state, Mexico, in four agrarians centers, two ejidos, Ejido of Tlacolula de Matamoros and Tanivet; and two communities, Tlacolula de Matamoros and San Marcos Tlapazola, data collection was through semi-structured interviews with participation in general meetings of each agrarian core. It was determined that the normally assumed history, not entirely correspond to the construction of the notions of ejido and community, especially the origin of social property, which historians relate it to el calpulli of previous civilizations to the colonization of the Central Highlands of Mexico, besides this, that legislation with the two concepts is based as if the land were provided - in the case of the ejidos, with parceled land of the "Haciendas"- or restituted, in this case, are the lands of indigenous peoples who they possessed documentary evidence that were donated by the spanish crown in which it was recognized that owned their land since time immemorial, keeping, the communal state that has to do with the preservation of their traditions and customs; it was found that the distribution of ejidos and communities and their dynamics is not as established by law and history, indigenous communities are not represented by the agrarian community, and most of the territory with presence of indigenous is ejido; multiple-case study found that the agrarian centers meet stipulated by the law to some extent, especially to have their papers in order and in accordance with the directions of agrarian institutions, but in practice, the study showed that the agrarian centers set their own functioning according to their traditions and adapt to the reforms of agrarian law without knowing the legal terminology, and build their own story based on their worldview. It is concluded that both politicians, intellectuals and legislators, write history and the law - in agrarian matters - without studying the reality of these within the ejidos and communities.